Relationship Between Rate Of Promotion And Perceived Organizational Political Climate - Cheah, Ken Cheong (1998)
The objective of this study was to investigate the relationship between employees' rate of promotion and their perception of organizational political climate in atechnology based American multinational corporation located in Bayan Lepas Free Industrial Zone, Penang, Malaysia. The study also examined the influences of moderating variables like age, marital status, gender and job status on the relationship.